Housing satisfaction and its correlates: a quantitative study among residents living in their own affordable apartments in urban Hanoi, Vietnam. Issue 1 (2nd January 2018) - Nguyen, Anh Tuan; Tran, Tuyen Quang; Vu, Huong Van; Luu, Dat Quoc
ABSTRACT: Using a novel dataset involving 450 respondents living in their own affordable apartments in urban Hanoi, this study examines the housing satisfaction of the respondents and its correlates. We find that housing satisfaction is positively associated with household income but negatively related to education. Interestingly, the study finds that residents borrowing from banks to buy a home are less satisfied with their home than their non-borrowing counterparts. We also find that respondents' positive evaluation of features of their apartments, such as the design, construction quality and price, is strongly linked with housing satisfaction. In addition, the location of the house and quality of the environment in the area were found to be major factors affecting housing satisfaction.